Peningkatan Kualitas Sumber Daya Insani melalui Pembelajaran Berbasis Kompetensi di Pabrik Tahu Zhuan Kim Jombang - Siti Ria Kurniawati; Dwi Puji Rahayu; Andriani Andriani (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Improving the quality of Human Resources (HR) is a crucial factor in supporting the performance of the food processing industry. This study aims to explore the application of Competency-Based Learning (CBL) in enhancing HR quality at Zhuan Kim Tofu Factory in Jombang Regency. A case study method with a qualitative approach was employed through observations and in-depth interviews with factory employees and management. The results indicate that the implementation of CBL significantly improves workers’ technical skills, deepens their understanding of production processes, and boosts work motivation. Additionally, CBL contributes to reducing error rates in the production process. These findings suggest that consistent implementation of CBL can serve as an effective strategy for managing human resources in the tofu processing industry.